2021
DOI: 10.1038/s41598-020-79385-w
|View full text |Cite
|
Sign up to set email alerts
|

Potentiality of multiple modalities for single-cell analyses to evaluate the tumor microenvironment in clinical specimens

Abstract: Single-cell level analysis is powerful tool to assess the heterogeneity of cellular components in tumor microenvironments (TME). In this study, we investigated immune-profiles using the single-cell analyses of endoscopically- or surgically-resected tumors, and peripheral blood mononuclear cells from gastric cancer patients. Furthermore, we technically characterized two distinct platforms of the single-cell analysis; RNA-seq-based analysis (scRNA-seq), and mass cytometry-based analysis (CyTOF), both of which ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 49 publications
(58 reference statements)
0
18
0
Order By: Relevance
“…Compared to scRNA‐seq, CYTOF offers the advantage of a higher throughput for the evaluation of the TME in clinical samples, as it allows for a more accurate targeting of immune cell subsets through the use of >30 selected antigen markers. Moreover, CyTOF “narrow and distinct” 78 , 79 data are generated from the analysis of over 250 000 cells, whereas transcriptome‐based platforms detect wider unbiased populations from several thousands of cells. 80 , 81…”
Section: Discussionmentioning
confidence: 99%
“…Compared to scRNA‐seq, CYTOF offers the advantage of a higher throughput for the evaluation of the TME in clinical samples, as it allows for a more accurate targeting of immune cell subsets through the use of >30 selected antigen markers. Moreover, CyTOF “narrow and distinct” 78 , 79 data are generated from the analysis of over 250 000 cells, whereas transcriptome‐based platforms detect wider unbiased populations from several thousands of cells. 80 , 81…”
Section: Discussionmentioning
confidence: 99%
“…CyToF is a mass cytometry method that analyzes multiple proteins tagged with labels. It has previously been alternatively used or combined with scRNA-seq in cancer immunity studies [3,20]. For example, single-cell mass cytometry (CyToF) is commonly used to classify cell surface proteins of immune cells into specific cell classifications.…”
Section: Single-cell Sequencing Technologies and Integrated Databasesmentioning
confidence: 99%
“…They found that pre-existing TILs were neither activated nor expanded after PD-1 blockade; instead, novel T cell clones appeared to undergo sequential reactions. GAPF REE2 consortium, including the authors of this manuscript, also conducted scRNA-seq using clinical samples from gastrointestinal cancer patients to characterize the transcriptome features of a series of cells constructing cancers, primarily focusing on immune cells [15] (Fig. 1a).…”
Section: Single-cell Analysis For Characterizing Microenvironmental Non-tumor Cellsmentioning
confidence: 99%